Risk factors and functional abnormalities associated with adult onset secondary nocturnal enuresis in women. Issue 1 (16th October 2015) - Madhu, Chendrimada K.; Hashim, Hashim; Enki, Doyo; Drake, Marcus J.
Abstract : Aims: The study aims to evaluate bothersome lower urinary tract symptoms (LUTS), risk factors, and associated functional abnormalities in women reporting adult onset secondary nocturnal enuresis (SNE), to help understand factors associated with SNE. Methods: 12, 795 women (age >18) attending a tertiary referral centre underwent a comprehensive standardized evaluation including urodynamic testing in accordance with the International Continence Society recommendations. Records of all patients reporting bedwetting while asleep were evaluated under various categories. Multiple logistic regression was used to identify statistically significant risk factors and urodynamic findings associated with SNE. Results: The prevalence of SNE in women undergoing urodynamic testing for bothersome LUTS was 14.4% (1, 838). High BMI (OR = 1.47, P  < 0.001), cigarette smoking (OR = 2, P  < 0.001), antidepressant usage (OR = 1.8, P  < 0.001), neurological conditions (OR = 2.12, P  < 0.001), and previous hysterectomy (OR = 1.19, P  = 0.03) were significantly associated with SNE. Women with SNE significantly complained of overactive bladder (OAB) symptoms (OR = 1.65, P  < 0.001) and slightly higher mean nocturia episodes (OR = 1.38, P  < 0.0001). Low maximum urethral closure pressure (MUCP) (OR = 1.34, P  < 0.0001) and detrusor overactivity incontinence (DOI) (OR = 1.75, P  < 0.0001) were significantly associated with SNE. There was no significant association with the symptom of stress urinary incontinence ( P  = 0.264), urodynamic stress incontinence ( P  = 0.454) or detrusor overactivity ( P  = 0.231). Conclusion: Women with adult SNE usually present with OAB symptoms. SNE is associated with high BMI, cigarette smoking, antidepressant use, and neurological conditions. DOI and a low MUCP are possible pathophysiological mechanisms in SNE. Neurourol. Urodynam. 36:188–191, 2017 . © 2015 Wiley Periodicals, Inc.